Manajemen Kekeringan Berbasis Desa: Strategi Pemerintah Desa Aska dalam Siklus Penanggulangan Bencana - Abd Wahid; Ahrah Mardiah; Hasdinawati (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study analyzes the strategy of the Aska Village Government in responding to drought using the disaster management cycle. The study was motivated by the 2023 El-Nino phenomenon, which triggered clean water scarcity, agricultural disruption, and household economic pressure. A descriptive qualitative approach was applied through observation, interviews, and documentation. The findings show that pre-disaster efforts included PAMSIMAS, SPAM, retention wells, and early warning dissemination. During emergency response, the village government identified water sources and provided pumps. In the post-disaster phase, it distributed food assistance and planned bore wells and additional retention wells. The main impacts were crop failure, plant mortality, drying water sources, increased water costs, cracked soil, and livestock feed shortages. Community self-reliance supported the strategy, while miscommunication, limited funding, and underperforming water facilities constrained it.